Pregnancy and risk of COVID‐19: a Norwegian registry‐linkage study. (1st November 2021) - Magnus, MC; Oakley, L; Gjessing, HK; Stephansson, O; Engjom, HM; Macsali, F; Juliusson, PB; Nybo Andersen, A‐M; Håberg, SE
Abstract : Objective: To compare the risk of acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and contact with specialist healthcare services for coronavirus disease 2019 (COVID‐19) between pregnant and non‐pregnant women. Population or sample: All women ages 15–45 living in Norway on 1 March 2020 ( n = 1 033 699). Methods: We linked information from the national birth, patient, communicable diseases and education databases using unique national identifiers. Main outcome measure: We estimated hazard ratios (HR) among pregnant compared to non‐pregnant women of having a positive test for SARS‐CoV‐2, a diagnosis of COVID‐19 in specialist healthcare, or hospitalisation with COVID‐19 using Cox regression. Multivariable analyses adjusted for age, marital status, education, income, country of birth and underlying medical conditions. Results: Pregnant women were not more likely to be tested for or to a have a positive SARS‐CoV‐2 test (adjusted HR 0.99; 95% CI 0.92–1.07). Pregnant women had higher risk of hospitalisation with COVID‐19 (HR 4.70, 95% CI 3.51–6.30) and any type of specialist care for COVID‐19 (HR 3.46, 95% CI 2.89–4.14). Pregnant women born outside Scandinavia were less likely to be tested, and at higher risk of a positive test (HR 2.37, 95% CI 2.51–8.87). Compared with pregnant Scandinavian‐born women, pregnant women with minority background had a higher risk of hospitalisation with COVID‐19 (HR 4.72, 95% CI 2.51–8.87). Conclusion: Pregnant women were not more likely to be infected with SARS‐CoV‐2. Still, pregnant women with COVID‐19, especially those born outside of Scandinavia, were more likely to be hospitalised. Tweetable abstract: Pregnant women are at increased risk of hospitalisation for COVID‐19. Tweetable abstract: Pregnant women are at increased risk of hospitalisation for COVID‐19.